Issue of Scarce Water Resources in the Najran Region: Reasons and Solutions from the Perspective of Islamic Jurisprudence and Laws within the Framework of Saudi Arabia’s Vision 2030 - El-Sayed Abu El-Ala, Khaled Fouad; Hindi Al-Sayed, Muhammad Ali Abu (Journal of Neonatal Surgery, 2025)
The residents of the Najran region face the problem of water scarcity due to the depletion of many underground wells, insufficient rainfall, and exacerbation caused by the mismanagement of water resources and outlets, as well as significant wastage during use. This includes traditional agricultural methods and the underutilisation of rainfall and floodwaters. This research examines the causes of the problem and proposes suitable solutions, framed within an environmental, jurisprudential, and legal study that aligns with Saudi Arabia's ambitious Vision 2030. This vision aims to strengthen the country's economy and provide essential life resources in its cities, including clean, fresh water. The primary objectives of this research are: Providing Islamic legal answers to questions related to water scarcity in the Najran region. Identifying a set of proposed solutions. Demonstrating the ability of Islamic jurisprudence to address and resolve emerging challenges in people's daily lives. The research concludes with several scientific findings detailed at the end of the study. It also presents a number of important recommendations, which are outlined at the end of the research and are closely related to its subject matter.